Alimentación de Spodoptera eridania (Lepidoptera: Noctuidae) en genotipos de soya - Sardinha de Souza, Bruno Henrique [UNESP]; Boiça Júnior, Arlindo Leal [UNESP]; Janini, Júlio Cesar [UNESP]; da Silva, Anderson Gonçalves [UNESP]; Lobato Rodrigues, Nara Elisa [UNESP] (My University, 2012)
This work aimed to find soybean genotypes with low feeding preference by Spodoptera eridania larvae on 23 genotypes evaluated in three experiments, of which iAC 100 was established as the resistant genotype and Br 16 as the susceptible genotype. From the results obtained in these tests, a final experiment was carried out with the 10 most outstanding genotypes: iAC 100, Pi 227682, Pi 227687, DM 339, P 98Y51 rr, BrSGO 8360, iGrA rA 518 rr, iGrA rA 516 rr, iGrA rA 626 rr and Br 16. in all experiments, free choice and no choice tests were performed. in the former, leaf discs corresponding to the genotypes were placed in Petri dishes and then one third-instar larva per genotype was released. in the latter we used one leaf disc of each genotype per plate where one third-instar larva was released. the attractiveness of the third-instar larvae was evaluated at 1, 3, 5, 10, 15, 30, 60, 120, 360, 720 and 1080 minutes after their release, as well as the leaf area consumed. in both tests the genotype iAC 100 was the least attractive and consumed by the larvae, whereas BrSGO 8360 and P 98Y51 rr were the most consumed in free choice and no choice tests, respectively. Genotype iAC 100 was highly resistant to S. eridania in feeding preference experiments and thus can be cultivated or incorporated into breeding programs in order to obtain soybean plants with resistance characteristics to this pest.
Feeding of Spodoptera eridania (Lepidoptera: Noctuidae) on soybean genotypes
Keywords: Attractiveness; Glycine max; Host plant resistance; Southern armyworm